2009
DOI: 10.1016/j.pain.2008.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Repeated dosing of ABT-102, a potent and selective TRPV1 antagonist, enhances TRPV1-mediated analgesic activity in rodents, but attenuates antagonist-induced hyperthermia

Abstract: Transient receptor potential vanilloid type 1 (TRPV1) is a ligand-gated ion channel that functions as an integrator of multiple pain stimuli including heat, acid, capsaicin and a variety of putative endogenous lipid ligands. TRPV1 antagonists have been shown to decrease inflammatory pain in animal models and to produce limited hyperthermia at analgesic doses. Here, we report that ABT-102, which is a potent and selective TRPV1 antagonist, is effective in blocking nociception in rodent models of inflammatory, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
134
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(143 citation statements)
references
References 33 publications
9
134
0
Order By: Relevance
“…Correcting for free fraction reveals that a free concentration of 39 nM relative to the capsaicin IC 50 of 10.0 nM and the acid IC 50 of 19.8 nM is sufficient to elevate core body temperature. Temperature elevation became evident within 15 min and persisted until the lead compound was cleared, an observation similar to that reported for 30 mol/kg ABT-102 (approximately 0.6°C; Honore et al, 2009). Like ABT-102, other TRPV1 antagonists that effectively block acid activation of the channel also significantly increase body temperature (Table 4).…”
Section: Downloaded Fromsupporting
confidence: 83%
See 2 more Smart Citations
“…Correcting for free fraction reveals that a free concentration of 39 nM relative to the capsaicin IC 50 of 10.0 nM and the acid IC 50 of 19.8 nM is sufficient to elevate core body temperature. Temperature elevation became evident within 15 min and persisted until the lead compound was cleared, an observation similar to that reported for 30 mol/kg ABT-102 (approximately 0.6°C; Honore et al, 2009). Like ABT-102, other TRPV1 antagonists that effectively block acid activation of the channel also significantly increase body temperature (Table 4).…”
Section: Downloaded Fromsupporting
confidence: 83%
“…The channel is activated by noxious stimuli, most notably capsaicin, the pain-producing agent of hot peppers, endogenous activators, such as NADA (Huang et al, 2002), heat (Ͼ 43°C), and protons (pH Ͻ 6.0) (Caterina et al, 1997). Genetic ablation and pharmacological blockade (Caterina et al, 2000;Gavva et al, 2005;Honore et al, 2005Honore et al, , 2009Cui et al, 2006) have confirmed a role for TRPV1 as a molecular integrator of painful stimuli from the periphery to the central nervous system. Considerable effort has been directed toward developing TRPV1 antagonists as novel antinociceptive agents.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…After behavioral testing, the morphine antagonist naloxone (0.1 mg/kg, diluted in saline, Naloxon Inresa, Inresa Arzneimittel GmbH, Freiburg, Germany) was injected intraperitoneally and after 30 minutes the entire behavioral testing procedure was repeated. Although it is impossible to check the exact dose that induces, analgesia in rats, we determined the doses based on the dose-response curves in behavioral assays 21,22) interpolation for humans data, 23) and according to the guidelines from Anesthesia and Analgesia in Laboratory Animals handbook. 24) Tissue harvesting and processing: After the completion of behavioral tests, the rats were anesthetized as previously described and sacrifi ced by decapitation.…”
Section: Methodsmentioning
confidence: 99%
“…Based on experiments in rodent models, including those of cancer and inflammation (Pomonis et al, 2003;Asai et al, 2005;Gavva et al, 2005b;Ghilardi et al, 2005;Honore et al, 2005Honore et al, , 2009, the TRPV1 channel has been explored as a novel target for analgesic therapy (Immke and Gavva, 2006;Szallasi et al, 2007;Gavva, 2008;Holzer, 2008;Gunthorpe and Chizh, 2009;Khairatkar-Joshi and Szallasi, 2009). The possibility of making next-generation pain therapeutics has stimulated immense interest, and many pharmaceutical companies all over the world have entered the race to synthesize and test TRPV1 antagonists.…”
Section: Pharmacological Antagonists Of the Transient Receptor Potmentioning
confidence: 99%